Applying Citizens' Juries to the global South: Survey measures to elicit the transformative potential of Citizens' Juries - Nilgen, Marco; Burger, Max; Vollan, Björn (CGIAR System Organization, 2024)
The scientific goal of conducting the Citizens' Jury is threefold: First, we rigorously evaluate whether participation in the Citizens’ Jury improves aspects important for civic engagement in the political process via changes in personal capabilities and perception (RQ1). Second, we describe the process of the Citizens’ Jury with respect to intra-personal perception of the progress and results and inter-personal dynamics throughout the process, before bringing both in relation to the policy proposals gained (RQ2). Third, we test how the resulting policy proposals are perceived in terms of adequacy and legitimacy by the general public, stakeholders, and policymakers (RQ3). While for the answering of RQ1, we rely on survey measures only, we apply both quantitative and qualitative methods to shed light on RQ2 and RQ3. This document provides an overview of the research questions to be tested and the methods applied.